Effects of probiotics on anxiety, stress, mood and fitness of badminton players - Salleh, R. M.; Kuan, G.; Aziz, M. N. A.; Rahim, M. R .A.; Rahayu, T.; Sulaiman, S.; Kusuma, D. W. Y.; Adikari, A. M. G. C. P.; Razam, M. S. M.; Radhakrishnan, A. K.; Appukutty, M. (Nutrients, 2021)
Background: Reports of probiotic consumption on athletes` performance are debatable due to their equivocal results. There is a need for more evidence on the effects of probiotic intake on psychological state and fitness level. Thus, this study determined the effects of daily probiotic consumption on competitive anxiety, perceived stress and mood among university badmintonplayers, besides their fitness like aerobic capacity, strength, speed, leg power and agility. Methods: Thirty university badminton players aged from 19 to 22 years old were randomly divided equally intotwo groups, where the probiotic group (PG;n= 15) received a drink that contained Lactobacillus casei Shirota (3×1010CFU) and placebo group (CG;n= 15) a placebo drink for six weeks. Anxiety, stressand mood levels were determined using the CSAI-2R, PSS and BRUMS questionnaires, respectively. Fitness levels were measured using by subjecting the players to 20-m shuttle runs (aerobic capacity),handgrips (muscular strength), vertical jumps (leg power), 40-m dash (speed) and T-test (agility). TheStudent`st-test (p< 0.05) was used to determine the differences between PG and CG players. Results:After six weeks, the anxiety and stress levels of PG players significantly decreased by 16% (p< 0.001)and 20% (p< 0.001), respectively, but there were no significant changes detected in CG players. Supplementation of probiotics also improved aerobic capacity in PG players by 5.9% (p< 0.001) butdid not influence the speed, strength, leg power and agility. Conclusions: Probiotics supplementation showed improved aerobic capacity and relieve anxiety and stress. However, further studies need tobe carried out to determine the mechanisms through which probiotic intake produces these effects.